2020
DOI: 10.3389/fpls.2020.00876
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Plant Architecture in Oryza Driven by the PROG1 Locus

Abstract: The genetic control of plant architecture in crops is critical for agriculture and understanding morphological evolution. This study showed that an open reading frame (ORF) of the rice domestication gene PROG1 appeared 3.4-3.9 million years ago (Mya). Subsequently, it acquired a novel protein-coding gene function in the genome of O. rufipogon (˜0.3-0.4 Mya). This extremely young gene and its paralogous C2H2 genes located nearby define the prostrate architecture of O. rufipogon and, thus, are of adaptive signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Blast searches indicated that key tiller-angle-regulating genes reported in rice and other plants, including PROG1 , LA1 , and TAC1 , were highly conserved in C. dactylon ( Figure 5B ). Similar to prostrate growing wild rice species, clustering of PROG1 -like C 2 H 2 transcription factor genes in adjacent positions of chromosomes were observed in C. dactylon ( Wu et al, 2018 ; Huang et al, 2020 ; Figure 5C and Supplementary Figure S15 ). By contrast, LA1 -like genes that promote erect growth not only experienced gene copy lost due to large chromosomal fragment deletions but also mutated to form truncated proteins ( Figure 5D and Supplementary Figure S16 ).…”
Section: Discussionmentioning
confidence: 66%
“…Blast searches indicated that key tiller-angle-regulating genes reported in rice and other plants, including PROG1 , LA1 , and TAC1 , were highly conserved in C. dactylon ( Figure 5B ). Similar to prostrate growing wild rice species, clustering of PROG1 -like C 2 H 2 transcription factor genes in adjacent positions of chromosomes were observed in C. dactylon ( Wu et al, 2018 ; Huang et al, 2020 ; Figure 5C and Supplementary Figure S15 ). By contrast, LA1 -like genes that promote erect growth not only experienced gene copy lost due to large chromosomal fragment deletions but also mutated to form truncated proteins ( Figure 5D and Supplementary Figure S16 ).…”
Section: Discussionmentioning
confidence: 66%
“…However, the majority of legumes have a semi-prostrate habit, where both HFP and trigonometric prediction of stem position with pods at harvest have to be taken into consideration (Ramteke et al, 2012). It is important to note that the erect-prostrate type of stem growth has independent genetic mechanisms (Upadhyaya et al, 2017;Zhang B. et al, 2017;Huang et al, 2020). However, recent results revealed that two auxin-related genes (transporter and transport inhibitor) were more active in plants with a prostrate habit than those with erect stems in plants of the perennial legume Astragalus adsurgens Pall., a Chinese native forage crop (Ma et al, 2020).…”
Section: -29mentioning
confidence: 99%
“…Interestingly, many GN-associated genes were involved in the regulation of other domestication related traits. PROG1 ( PROSTRATE GROWTH 1 ) is a key gene in the process of rice domestication, which controls the critical transition from prostrate to erect growth, and changes the plant architecture ( Tan et al, 2008 ; Huang et al, 2020 ). PROG1 is predominantly expressed in the axillary meristems, and promotes GN through increasing the number of primary and secondary branches ( Jin et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%